Os sentidos de povo nos pronunciamentos presidenciais de posse: de 1985 a 2011 - Luz, Marcelo Giovannetti Ferreira (2014)
We aim with this dissertation, conduct an analysis of discursive pronouncements tenure of the presidents of the Republic, in order to ascertain the effects of meaning of the word "people" produced in these speeches, along with the images of themselves that every president conveys, in building "us "political as well as the image of the auditorium of these pronouncements. For this, we take as our research corpus pronouncements tenure of presidents Tancredo Neves (1985), José Sarney (1985), Fernando Collor de Melo (1990), Franco (1992), Fernando Henrique Cardoso (1994, 1999), Luiz Inácio Lula da Silva (2003, 2007) and Dilma Rousseff (2011). For this, we take as our research corpus pronouncements tenure of presidents Tancredo Neves (1985), José Sarney (1985), Fernando Collor de Melo (1990), Franco (1992), Fernando Henrique Cardoso (1994, 1999), Luiz Inácio Lula da Silva (2003, 2007) and Dilma Rousseff (2011). We promote a brief characterization of the political discourse, we make a theoretical route, introducing some important caveats to our analysis of its operation. Thus, we try to show how it gives the relationship of what is meant by politics and what became known as political discourse. A third point to be addressed is the formation of identities and the legitimacy and political discourse in an attempt to better understand the subject that gives the president the power to say. Then, by considering the pronouncement presidential inauguration ritual that requires a specific discourse genre, we briefly discuss about some considerations about the discourse genre, topic that is discussed further in the discussion of specific genres and ritual part, we make a parallel between the ritual inauguration and gender pronouncement of possession. To help us meet our analyzes, we present a discussion of the notion of Production Conditions of discourse in order to show how this concept becomes productive for understanding the production of meanings in the discourse. Having analyzed the senses of people present in the above pronouncements of possession, promote, in the third chapter, an analysis of how the image is constructed in these presidential speeches, with reference to the meanings produced for "people" in the previous chapter, ie, how the subjects presidents create an image of themselves in relation to the senses of the people present in his speech. At the conclusion of this work, one can see that the sense of "people" acquires a watery consistency, slipping widely not only from a speech to another, as even within a single discourse, producing effects of various senses, which corroborates the assertion that these senses, this division does not watertight, but acquires new and constantly different contours.